The Utilization of the Independent Learning Platform (PMM) in Supporting Science Learning and the Implementation of the Independent Curriculum - Agus Waldi; Rayendra; Zelhendri Zen; Fetri Yeni J (Jurnal Penelitian Pendidikan IPA, 2025)
I The implementation of the Independent Curriculum through the use of the Independent Teaching Platform (PMM) at SMK Negeri 6 Padang faces a number of challenges, such as teachers' lack of understanding of the curriculum, limited content in the PMM feature, and limited internet access in schools. This study aims to analyze the use of self-development, teaching, and inspiration features in the implementation of the Independent Curriculum in vocational schools. The results showed that although teachers have taken advantage of the PMM feature, only a few features such as self-training, performance management, CP/ATP, teaching tools, and inspirational videos are used optimally, while other features have not been maximized due to limited content and are still in the development stage. Factors that support the use of PMM include professional development features, collaboration in the development of teaching materials, and career opportunities, while obstacles faced include limited technology skills, limited time, and lack of motivation for teachers to participate in training. To overcome these barriers, it is necessary to conduct regular training to improve teachers' digital skills, proportionate workload management, improve PMM features, and develop materials relevant to learning needs, as well as increase teachers' awareness that training and seminars are not just for certification.